(untitled) (Intent Research Scientific Journal, 2023)
Nowadays, building materials must not only meet the criteria of functional performance but also reduce their impact on the environment along with their production. Among the wide range of reinforcement types, basalt fibers are included as an alternative to the widely used steel fibers. The benefits associated with low-energy production indicate that this material can be used very well in terms of functional properties and, at the same time, reduce the environmental burden. There is very limited information on the actual environmental impact of using basalt fibers. To fill this gap, it describes the environmental impacts associated with the production of basalt fibers. An analysis combining functional and ecological indicators was performed to provide a more reliable and consistent view. The use of basalt reinforcement provides a significantly lower environmental intensity per unit of force, especially in compressive and bending strength.